2024
DOI: 10.3390/educsci14040352
|View full text |Cite
|
Sign up to set email alerts
|

Student Player Types in Higher Education—Trial and Clustering Analyses

Lea C. Brandl,
Andreas Schrader

Abstract: In the context of the ongoing transformation in education, new learning methods, as well as new technologies, and therefore new forms of interactions are challenging higher education. This challenge can be addressed through ambient learning management systems that adapt to the student in the presentation and preparation of course materials. For educational games offered in such systems, this means that the game mechanics should be adapted to the student. To narrow down the sum of mechanics to the amount that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In addition, recent research emphasized the importance of tailoring game mechanics to individual types of players. For example, a study conducted at the University of Lübeck identified three player profiles using Marczewski's Hexad Framework [57] and recommended specific mechanics for each profile to improve the effectiveness of educational games [58]. Despite the open debate about potential taxonomies, considering player profiles in the design of educational games can improve their effectiveness, foster deeper understanding, and support interest and engagement in STEM education [59].…”
Section: Methodological and Theoretical Considerations In Gbl Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, recent research emphasized the importance of tailoring game mechanics to individual types of players. For example, a study conducted at the University of Lübeck identified three player profiles using Marczewski's Hexad Framework [57] and recommended specific mechanics for each profile to improve the effectiveness of educational games [58]. Despite the open debate about potential taxonomies, considering player profiles in the design of educational games can improve their effectiveness, foster deeper understanding, and support interest and engagement in STEM education [59].…”
Section: Methodological and Theoretical Considerations In Gbl Researchmentioning
confidence: 99%
“…As delineated in the "Methodology" section, the employment of quantitative textual analysis of titles and abstracts from academic publications over a specified period facilitated the identification and examination of trends and patterns within the academic landscape, thereby fostering a comprehensive grasp of the subject matter. Indeed, co-word analysis proved exceptionally adept at capturing the dynamic nature of research trends [57,58]. Moreover, this method enabled a more profound comprehension of the interrelationships among various research themes, offering a detailed depiction of the evolution of GBL in STEM education for secondary schools during the observed timeframe.…”
Section: Validating the Application Of Co-word Analysis As A Bibliome...mentioning
confidence: 99%